The Relations Between Tutor Learning Strategy With Learning Performance in Equivalency Program Paket B - Hayatul Husna; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the low learning outcomes of social science subjects for equivalence education package B at PKBM Suka Maju Sejahtera, Padang City. This can be seen from the learning strategy provided by the tutor is not good so that it affects the learning outcomes of learning residents. The objectives of the research are: (1) to see the description of the tutor's learning strategy (2) to see the description of the learning outcomes obtained by the learning community; and (3) to find out the relationship between tutor learning strategies and learning outcomes for social studies subjects in equivalence education package B.  This research is classified as quantitative with correlational type. The population in this study were 20 people, the sampling technique was in the form of random sampling and taken as much as 100% or all of those included in the population would be used as a sample of 20 people. The data collection technique uses a questionnaire with the tool in the form of a list of statements. The data were analyzed by the percentage formula and the data processing technique used the rank order formula. The results of this study are: (1) tutor learning strategies at PKBM Suka Maju Sejahtera Padang City are categorized as low. (2) the learning outcomes of social studies subjects are categorized as low. (3) there is a significant relationship between the tutor's learning strategy and the learning outcomes of social studies subjects for equivalence education package B at PKBM Suka Maju Sejahtera, Padang City. It is hoped that further researchers will be able to innovate by examining other variables.